A responsabilidade civil na modalidade de entrega delivery das empresas formais e informais de Sobral (CE) - Feijó, José Joel Linhares (My University, 2022)
This study aimed to analyze the type of civil liability in the delivery modality of formal and informal companies in the municipality of Sobral (CE) in the event of an accident, be it traffic or another harmful event. As for the method, the research has a generic qualitative approach of an exploratory nature that investigated the level of knowledge of businessmen and managers about civil liability in the practices of hiring motoboys (motorcycle freight operators) and motoboys perception about their roles as a representative of the company for which they work. The research subjects were eight motorcycle couriers, who provide their services in different ways, and ten businessmen and managers who take the services. The research was operationalized through a semi-structured interview followed by a content analysis with three chronological steps: pre-analysis, material exploration, treatment of results/inference/interpretation. It was observed that most motoboys work precariously without personal insurance, without Personal Protective Equipment (PPE), with old motorcycles and without knowing the federal and municipal legislation of Sobral (CE) that regulate the profession of motoboy/motorcycle freight. As a result, there is lack of knowledge regarding obligations and civil liability regarding delivery activity, both on the part of entrepreneurs and motoboys, in case of a harmful event enroute to delivery. [resumo fornecido pelo autor]
Este estudo teve como objetivo analisar qual o tipo de responsabilidade civil na modalidade de entrega delivery das empresas formais e informais do município de Sobral (CE) em caso de acidente, seja de trânsito ou outro evento danoso. Quanto ao método a pesquisa tem uma abordagem qualitativa genérica de caráter exploratório que investigou o nível de conhecimento de empresários e gestores sobre a responsabilidade civil nas práticas de contratação de motofretistas e o grau de percepção do motofretista sobre seu papel de representante da empresa para a qual faz a entrega. Os sujeitos da pesquisa foram oito motofretistas, que prestam seus serviços por diversas modalidades, e dez empresários e gestores tomadores dos serviços. A pesquisa foi operacionalizada por meio de uma entrevista semiestruturada seguida de uma análise de conteúdo com três polos cronológicos: pré-análise, exploração do material, tratamento dos resultados/ inferência/ interpretação. Observou-se que a maioria dos motoboys trabalham de forma precária sem seguro pessoal, sem EPIs, com motocicletas velhas e sem conhecerem a legislação federal e do município de Sobral (CE) que regulamentam a profissão de motoboy/motofrete. Em decorrência, constatou-se falta de conhecimento quanto às obrigações e responsabilidade civil na atividade de entrega delivery, tanto dos empresários quanto dos motoboys, em caso de um evento danoso que venha a ocorrer no percurso de entrega. [resumo fornecido pelo autor]
Keywords: Empresas - Sobral (CE); Entrega de mercadorias; Responsabilidade (Direito); Motoboys; Periculosidade (Direito); Business enterprises - Sobral (Brazil); Delivery of goods; Liability (Law); Danger (Law)